Phosphate Solubilizing Study on the Determination of Inoculant Dose and Composition for Biofossi Fertilizer - A. Citraresmini; E.T. Sofyan (PPIKSN-BATAN, 2018)
Phosphorus availability becomes a major problem on the productivity of soil and rice in Indonesia. Utilization of P source which has a slow release property is one of the solutions to these problems. Biofossi fertilizer is a natural phosphate organic fertilizer which is enriched with phosphate solubilizer bacteria (PSB), to improve the solubility of P and absorption by the plant so that P fertilization becomes more efficient. Experiment conducted on January 2015 at the experimental station of Agriculture Faculty-Padjadjaran University, Bandung, located in Ciparay, West Java. The aim of the experiment was to determine the PSB composition and its inoculation dose toward natural phosphate. Inoculum used was of Bacillus sp and Pseudomonas sp, which was injected to a carrier material. Through previous test results, the carrier used had a composition of 50 % peat + 28 % compost + 5 % humic acid + 2 % nutrition + 15 % rice husk. To test the dose of PSB inoculation, experimental design of factorial randomized complete block was applied. As the first factor was P2O5 content in the phosphate source, consisting of four levels as follows: (1) p0 = without P2O5 (as control); (2) p1 = 22 % P2O5 (163 kg ha-1 natural phosphate from Blora); (3) p2 = 26 % P2O5 (138 kg ha-1 natural phosphate from Morocco); (4) p3 = 36 % P2O5 (100 kg ha-1 SP-36 fertilizer). Second factor was the combination of dose and type of PSB inoculant, consisting of seven levels as follows: (1) b0 = without inoculation of PSB (as control); (2)b1 = Bacillus sp inoculant in the dose of 1 kg ha-1; (3)b2 = Bacillus sp inoculant in the dose of 2 kg ha-1; (4) b3 = Pseudomonas sp inoculant in the dose of 1 kg ha-1; (5)b4 = Pseudomonas sp inoculant in the dose of 2 kg ha-1; (6)b5 = Bacillus sp + Pseudomonas sp consortium in the dose of 1 kg ha-1; (7) b6 = Bacillus sp + Pseudomonas sp consortium in the dose of 2 kg ha-1. By using the 32P radioisotope techniques it was known that a consortium of bacteria Bacillus sp + Pseudomonas sp was capable of dissolving P on the treatment p0, as well as in the treatments p1, p2 and p3. In this treatment, some of the highest response was obtained, i.e. the grain dry weight, P uptake and P fertilizer efficiency.